The Export Supply Of Indonesian Crude Palm Oil (CPO) To India - Marizha Nurcahyani; Masyhuri Masyhuri; Slamet Hartono (Agro Ekonomi, 2018)
Palm oil is one of the world's most consumed vegetable oils other than soybean oil, canola oil and sunflower seed oil. Indonesia is one of the largest CPO producers in the world, while India is the biggest consumer in Indonesia as well as in the world. This study was conducted to analyze the rate of Indonesia’s CPO export growth to India by using the annual data from 2003 to 2015 and the factors affecting Indonesia's CPO exports to India by using the annual data from 1990 to 2015. The method used is market share analysis by standard growth calculation to measure the growth rate and Error Correction Model (ECM) method to know the factors that give short-term and long-term effects. Factors tested in this study include international CPO prices, soybean oil prices, Malaysian CPO export duty and Indonesian CPO export duty. The analysis shows that the growth rate of Indonesian CPO exports to India is fluctuate and the export volume of Indonesian CPO to India is influenced by export duty of CPO Indonesia negatively and significantly in the long-term and short-term.